Ablation behavior under oxyacetylene torch of ZrC coating modified by SiC/TaC nanocomposites. (15th August 2022) - Zhang, Yuyu; Sun, Jia; Guo, Lingxiang; Zhang, Xuemeng; Cui, Dingcong; Fu, Qiangang
Abstract: Plasma-sprayed ZrC coating modified by polymer-derived SiC/TaC nanocomposite was prepared on SiC-coated carbon/carbon composites to improve the long-life ablation resistance ability. In terms of the modifiers in coatings, the SiC/TaC nanocomposites were more stable without being oxidized or molted obviously owing to the "TaC embedded in SiC" nanostructure. The thickness increase rate of SiC/TaC modified coating decreased by 41% compared with ZrC-SiC-TaC coating after ablation for 180 s. The improved ablation resistance was attributed to the thermally grown Zr6 Ta2 O17 and Ta2 O5, which inhibited crack propagation and promoted ZrO2 sintering, forming a dense and protective layer. Highlights: SiC/TaC nanocomposites were introduced into ZrC coating to improve its long-life ablation-resistant ability. SiC/TaC nanocomposites were structurally stable during spraying owing to the unique TaC embedded in SiC matrix. ZrC-SiC/TaC coating exhibited better ablation resistance than that of SiC-TaC mixed ZrC coating. Zr6 Ta2 O17 and Ta2 O5 could effectively inhibit crack propagation and promote sintering to form a dense oxide layer.